1997
DOI: 10.1046/j.1365-2141.1997.d01-2080.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of p67phox, p47phox or gp91phox in chronic granulomatous disease does not impair leucocyte chemotaxis or motility

Abstract: Summary. Chronic granulomatous disease (CGD) is a syndrome characterized by failure of the NADPH oxidase of phagocytes that generates superoxide, which is central to the microbicidal process. Cytosolic components of this oxidase system include the proteins p67 phox and p47 phox , deficiencies of which cause the autosomal recessive form of CGD, whereas the X-linked form of the disease is characterized by a deficiency in the plasma membrane component gp91 phox . Components of the oxidase system have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Chemotaxis was assessed by direct observation and recording of cell behavior in stable concentration gradients of CSF-1 using the Dunn chemotaxis chamber (Weber Scientific International Ltd., Teddington, UK). This apparatus permits the directions of migration of individual cells to be measured in relation to the direction of the gradient and the time course of the response to be followed ( Zicha et al, 1991 , 1997 b ). Details of the construction and calibration of the apparatus are given in Zicha et al (1991) and Webb et al (1996) .…”
Section: Methodsmentioning
confidence: 99%
“…Chemotaxis was assessed by direct observation and recording of cell behavior in stable concentration gradients of CSF-1 using the Dunn chemotaxis chamber (Weber Scientific International Ltd., Teddington, UK). This apparatus permits the directions of migration of individual cells to be measured in relation to the direction of the gradient and the time course of the response to be followed ( Zicha et al, 1991 , 1997 b ). Details of the construction and calibration of the apparatus are given in Zicha et al (1991) and Webb et al (1996) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies have demonstrated that mice lacking the p47 phox or gp91 phox subunits of NADPH oxidase exhibit higher neutrophil infiltration levels than WT mice (Gao et al, 2002; Pollock et al, 1995). However, directional neutrophil migration is either unaffected or reduced when ROS generation by neutrophils is inhibited (Hattori et al, 2010; Zicha et al, 1997). Thus, while neutrophil-generated ROS can regulate neutrophil migration, the underlying signaling mechanisms and ROS substrates that mediate neutrophil migration in response to chemoattractants have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the inability of CGD leukocytes to metabolize NO may render them more sensitive to its inhibitory effects. In vitro studies under NO-free conditions show that chemotaxis of neutrophils from CGD patients does not differ from healthy controls (60). However, decreased leukocyte adhesion and emigration in cholesterol-fed p47 phoxϪ/Ϫ mice and delayed monocyte or T cell migration into livers of Leishmania donovanii-infected gp91 phoxϪ/Ϫ mice indicate that lack of NADPH oxidase renders leukocytes less able to migrate during inflammation in vivo (6,7).…”
Section: Discussionmentioning
confidence: 99%